TALENT DEVELOPMENT IN THE WORLD OF CLASSICAL MUSIC AND VISUAL ARTS - Jarvin, Linda (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2017)
In this article, we propose to explore the developmental trajectories of children displaying gifts and abilities in the domains of (classical) music and in visual arts. A developmental model for talent development that was developed in the domain of classical music will be briefly presented and its applicability in the field of visual arts will be discussed.